Tau phosphorylation in cells transfected with wild-type or an Alzheimer's disease mutant Presenilin 1. - Irving, N; Miller, C (1997)
We have studied the effect of overexpressing either wild-type or an Alzheimer's disease mutant Presenilin 1 (PS1) on tau phosphorylation in transfected Chinese hamster ovary (CHO) and COS cells. Tau transfected into these cells is predominantly non-phosphorylated at many PHF-tau sites but co-transfection with the tau kinase glycogen synthase kinase-3 beta (GSK-3 beta) induces phosphorylation that generates epitopes for several phosphorylation-dependent antibodies. Co-transfection of tau with either wild-type or mutant PS1 did not alter tau phosphorylation as detected by five different antibodies. Likewise, co-transfection of the PS1s did not influence GSK-3 beta-mediated tau phosphorylation. The implications of these results for the pathogenesis of Alzheimer's disease are discussed.